A Financial Planning Decision Support System For Small Medium Enterprise - Pong, Chia Lee (2000)
This project is aimed at developing a low cost and end user oriented financial planning decision support system (DSS) for small medium enterprise (SME) in Malaysia. Low cost and user friendly DSS is essential to assist the SME decision makers in their future financial planning as the available financial planning software are too expensive and not compatible for the SME in Malaysia. An integration of Microsoft Excel 2000 and Microsoft Visual Basic 6.0 had been used to develop this system. The financial models had been developed using Microsoft Excel 2000 (spreadsheet based) and the user interfaces had been developed using Microsoft Visual Basic 6.0. Upon the system prototyping process, the system had been tested in an academic environment (Universiti Utara Malaysia). Further works such as extending the system to a full functional system and a group decision support system (GDSS) could be done to improve the functionality and feature of the system.